Strategic Improvement of New Electricity Connection Services for Residential Customers at PT PLN (PERSERO) UP3 Manado - Rompas Daniel Fidel; Bambang Syairudin (Journal Research of Social Science, Economics, and Management, 2025)
The demand for new electricity connection services at PT PLN (Persero) UP3 Manado continues to increase in line with the rapid growth of residential housing developments. The current payment model, which only requires one household to pay the connection fee upfront, further increases the risk of uncollected receivables and delays in network construction. This situation highlights the need for a more effective and integrated service improvement strategy. This study aims to formulate priority strategies for improving new electricity connection services for residential customers by considering internal and external factors, customer satisfaction levels, and the potential implementation of an innovative banking mechanism for payment transactions. A qualitative approach was employed through in-depth interviews with eight key informants from PT PLN (Persero) UP3 Manado and housing developers, supported by questionnaires to determine the weights and attractiveness scores (AS) in the SWOT and QSPM matrices. The findings reveal five dominant factors causing delays: limited availability of main distribution materials, repetitive administrative processes, unsynchronized payment mechanisms with construction progress, suboptimal internal coordination, and limited TMP monitoring. SWOT analysis generated ten alternative strategies, and QSPM results identified three priority strategies. The strategy with the highest total attractiveness score (7.03) is collaboration with banks to facilitate payment transactions, followed by partnership with housing developers (6.55), and development of an integrated new connection service (6.26). This research concludes that accelerating new electricity connections can be achieved by integrating innovative banking-based payment mechanisms, improving internal processes, and adopting digital technology support.